STRATEGIES FOR ADVANCING REGIONAL ORIGINAL INCOME DURING THE COVID-19 PANDEMIC IN THE OFFICE OF COOPERATIVES, MSMES, INDUSTRY AND TRADE IN BOALEMO REGENCY - Imam Mashudi; Sukrianto; hajarati, elan (Journal of Economic, Business, and Administration (JEBA), 2023)
The study aimed to develop a strategy for increasing regional original income during the Covid-19 pandemic at the Boalemo Regency's Office of Cooperatives, Small and Medium-Sized Enterprises, Industry, and Trade (Diskumperindag). The descriptive research method is combined with a qualitative approach in this study. The sample size for this study was 43 individuals. The study's findings indicated that; (1) The Office of Cooperatives, Small and Medium Enterprises, Industry and Trade of Boalemo Regency possesses several strengths, including the potential for significant regional retributions in the form of Regional Original Income, regional retribution rates that support Regional Original Income (PAD), local government and community support for Cooperatives, Small and Medium Enterprises, Industry and Trade, and the existence of a regional regulation that promotes regional original income. 2) Weaknesses that must be addressed include the absence of regional taxes, ineffective market management, and failure to attain the regional original income target. (3) Possibilities These include growing economic activity, government commitment and support, and the involvement and cooperation of multiple agencies in collecting Regional Original Revenue. 4) The threats include the following: Regional Original Income during the Covid-19 Pandemic, the installation of Large-Scale Social Restrictions during the Pandemic era I community awareness and support services, and community knowledge.